Optimalisasi Penghimpunan dan Penyaluran Zakat Melalui Unit Pengumpul Zakat (UPZ) Masjid Al-Hidayah Mandailing Natal (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2026)
Zakat is a key instrument in the Islamic economic system, functioning as a mechanism for income redistribution and poverty alleviation. However, zakat management at the level of mosque-based Zakat Collection Units (Unit Pengumpul Zakat/UPZ) still faces significant challenges, particularly in terms of managerial capacity, administrative systems, and institutional governance. This community service project aims to optimize the collection and distribution of zakat through capacity building of the UPZ management at Al-Hidayah Mosque, Mandailing Natal. The study employed a participatory approach consisting of observation, joint planning, socialization, training, mentoring, and evaluation stages. Data were collected using observation, interviews, and structured questionnaires administered through pre-test and post-test to measure participants’ knowledge improvement. Data analysis was conducted using a descriptive comparative method to assess changes before and after the intervention. The results indicate a significant improvement in the managerial capacity of UPZ administrators, as reflected by an increase in the average score from 55% in the pre-test to 80% in the post-test. In addition, improvements were observed in zakat management practices, including the establishment of simple financial recording systems, the development of a structured database of donors (muzakki) and beneficiaries (mustahik), and enhanced transparency and accountability. Qualitatively, the program also fostered behavioral change among administrators, the emergence of local leadership, and increased public trust in the UPZ. This study concludes that participatory-based socialization, training, and mentoring are effective in strengthening institutional capacity and optimizing zakat management at the grassroots level. The findings highlight the importance of governance and capacity building in enhancing the effectiveness of community-based zakat institutions.